Tiktok Virtual Communication Effectiveness on @Luxxlim.Id Account in Attracting Consumers in Elyo Store - Maulidia Ayu Cantika; Nursapiah Harahap (Jurnal Sains Sosio Humaniora, 2022)
This study is useful in the factors that affect the effectiveness of virtual communication through social media Tiktok to attract people's buying interest. As for answering these questions, using descriptive and qualitative methods. In other words, qualitative research provides a detailed description of the situation or process that is being investigated and is supported by the theory of Use and Effects unit of use and gratification and the traditional theory of effects or can also be defined as a theory that explains communication networks between mass media can lead to effects to internet users themselves. In addition to being supported by the Uses and Effects theory, virtual communication is part of the way to deliver messages, the steps are carried out via social media, through multiple accesses, updates/ interactive updates, and two-way communication. One user and another is carried out using cyberspace or virtual space which is generally interactive. The author reviews and then analyzes the results of research on the effectiveness of the virtual communication. In the research, this article results that the causes that make consumers buy virtual communications from Tiktok accounts are the image design used, the audio concept, and the video concept of the content.